Christian-Muslim dialogue in the Philippines, 1974-1982 : retrospect and prospect - Boosi, Suneel Bhanu, 1952 ([Manila] : South East Asia Graduate School of Theology, 1982)
More than three centuries of hostility between Christian Filipinos and Muslim Filipinos, involving extensive loss of life and damage to property, is one tragic aspect of the history of the Filipino people. This sad situation, which to some extent continue to this day, casts a dark shadow on the life of these two communities of faith which claim to be obedient to God's will and whose members profess that the essence of worship to God is care, concern and love for fellowmen. On the political sphere, the gulf between Muslim and Christian Flipinos has become an obstacle to the achievement of national unity, adversely affecting the order of society. In their daily lives, both Muslim and Christian Filipinos, particularly in Mindanao, encounter each other in everyday life situations. But their meeting is superficial, and the two communities of faith do not seem to recognize their independence on one another. Becasue of their long history of conflict, each side looks at the other with suspicion and distrust.
Thesis (M.Theo.) -South East Asia Graduate School of Theology